Interface‐Strengthened Polyimide/Carbon Nanofibers Nanocomposites with Superior Mechanical and Tribological Properties. Issue 14 (16th June 2014) - Zhu, Jiahua; Mu, Liwen; Chen, Long; Shi, Yijun; Wang, Huaiyuan; Feng, Xin; Lu, Xiaohua
<x xml:space="preserve">Abstract</x> A self‐assembling molecule, n‐octadecane phosphate, is successfully synthesized and used to modify the surface property of carbon nanofibers (CNFs). Both untreated CNFs (CNFs(u)) and treated CNFs (CNFs(t)) are incorporated in polyimide (PI) as filler to study the interfacialproperty‐determined thermal, mechanical, and tribological properties of their corresponding nanocomposites. At room temperature, the mechanical properties of PI/CNFs(t) including elongation‐to‐break, tensile strength, bending strength, and impact strength are remarkably improved by 150%, 29.4%, 26.7%, and 183%, respectively, in comparison with the PI/CNFs(u) composites. At 150 °C, the enhancement of the elongation‐to‐break reaches 250%, while the tensile and flexural‐strength enhancement reduce to 2.8% and 20.4%. In addition, the tribological properties of PI/CNFs(t) composite are also improved due to the better interfacial interaction between the filler and the matrix. Microstructure analysis of the fracture surface directly reveals the better dispersion quality of CNFs(t) in PI and superior interfacial adhesion with the introduced assembling layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>